2013
DOI: 10.1159/000353585
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Seven Genes Linked to Body Mass Index and Adiposity by Genome-Wide Association Studies: A Review

Abstract: Genome-wide association studies (GWAS) have identified a total of about 40 single nucleotide polymorphisms (SNPs) that show significant linkage to body mass index, a widely utilised surrogate measure of adiposity. However, only 8 of these associations have been confirmed by follow-up GWAS using more sophisticated measures of adiposity (computed tomography). Among these 8, there is a SNP close to the gene FTO which has been the subject of considerable work to diagnose its function. The remaining 7 SNPs are adja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 149 publications
0
49
0
Order By: Relevance
“…37). Although the effect has been attributed to the transmembrane protein 18 (TMEM18), a transcriptional repressor that sequesters sequences at the membrane, there is debate concerning whether TMEM18 is involved in obesity regulation through expression in adipose tissue or the central nervous system (38). The causative variant(s) remain unclear even after targeted resequencing efforts that focused mainly on the TMEM18 coding sequence (39)(40)(41); it is presumed that the risk haplotype contains a noncoding regulatory variant.…”
Section: Significancementioning
confidence: 99%
“…37). Although the effect has been attributed to the transmembrane protein 18 (TMEM18), a transcriptional repressor that sequesters sequences at the membrane, there is debate concerning whether TMEM18 is involved in obesity regulation through expression in adipose tissue or the central nervous system (38). The causative variant(s) remain unclear even after targeted resequencing efforts that focused mainly on the TMEM18 coding sequence (39)(40)(41); it is presumed that the risk haplotype contains a noncoding regulatory variant.…”
Section: Significancementioning
confidence: 99%
“…In addition, using the RegulomeDB website, rs10813121 in chromosome 9 was found to bind to seven proteins, among them STAT3 and Nrf-2, a key transcription factor that regulates antioxidant defense in macrophages and epithelial cells (35). The leucine-rich repeat and Ig domaincontaining 2 gene (LINGO2) is expressed in neuronal tissue, and variants have been associated with essential tremor and Parkinson's disease as well as obesity (36)(37)(38). The function of LINGO2 is currently unclear, and further investigation is needed to understand its potential role in the pathogenesis of airway responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Rs7498665 in SH2B1 is one of the SNPs initially identified in GWAS with significant linkage to BMI whose association has been confirmed by follow-up studies using computed tomography as a measure of adiposity [161]. With regard to its involvement in ED, and as in the case of the other BMI-related polymorphisms, Brandys et al could not find an association of rs7498665 with AN risk [127].…”
Section: Src-homology 2 Domain-containing Protein B1mentioning
confidence: 99%
“…In addition, the nutritional state has been shown in animal models to affect the expression of Etv5 in important areas for feeding behavior [180], although this overexpression did not translate into significant changes of eating habits [181]. In any case, it has been suggested that, being a transcription factor, the possibility that ETV5 influences energy balance by transcriptional regulation of key genes linked to food intake in the hypothalamus seems highly likely [161]. Interestingly, BDNF has been shown to have a principal role orchestrating ETV5-mediated cellular migration [182].…”
Section: Etv5 Transcription Factormentioning
confidence: 99%